1987
DOI: 10.1007/bf01421826
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism of polypropylene gels

Abstract: It is found that polypropylene gels in some solvents of benzene-derivatives show a striking change of colour. The colour changes from blue to yellow as the temperature rises from the melting point of the solvent to around 70-80 ~ The apparent characteristic of the phenomenon resembles the thermochromism of cholesteric liquid crystals although potypropylene itself is colourless and has no asymmetric carbons in the molecules. Polypropylene flakes swelled in these solvents also show similar thermochromism. [14][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Although the Shultz-Flory method is approximate, it has been widely applied by many authors. [47][48][49] The theta temperatures for many polymer-solvent systems obtained from the second virial coefficient and the Shultz-Flory methods are in good agreement, but W 1 values are insignificantly lower in the case of the Shultz-Flory method.…”
Section: Determination Of Critical Parameters In Thementioning
confidence: 99%
“…Although the Shultz-Flory method is approximate, it has been widely applied by many authors. [47][48][49] The theta temperatures for many polymer-solvent systems obtained from the second virial coefficient and the Shultz-Flory methods are in good agreement, but W 1 values are insignificantly lower in the case of the Shultz-Flory method.…”
Section: Determination Of Critical Parameters In Thementioning
confidence: 99%
“…1 This phenomenon is considered to be of importance in connection with the coloration mechanism. Figure 1 shows the transmittance spectra of 2 g/v-% of polypropylene gels in o-xylene after reaching equilibrium at 25 • C that had been prepared at various temperatures after being dissolved in the solvent at 160 • C.…”
Section: Spectra Of Polypropylene Gels and Conditions For Preparing Gelsmentioning
confidence: 99%
“…This coloring phenomenon has been considered to be due to selective light-scattering, as the transmitted-light spectra of the gels forms a rough reflected image of the scatteredlight spectra, which are measured in the direction perpendicular to the incident light. 1,2 We have more recently demonstrated that the development of coloration in polypropylene gels can be explained due to selective light-scattering on the basis of differences in the lightdispersive power between solvent and polypropylene, and to size-controlled polypropylene networks formed in the gel. [3][4][5][6][7][8][9][10][11] Furthermore, it has been experimentally proved that the thermochromic phenomenon in the gel can be explained consistently using the same logic.…”
mentioning
confidence: 99%
“…Previously [1] we reported the thermochromism of swelled and gelled isotactic polypropylene in some benzene-derivative solvents. It was revealed that the colouring phenomenon was due to selective scattering, but not to optical absorption.…”
Section: Introductionmentioning
confidence: 99%